Influence of Television Political Programmes on Votersâ€™ Opinion in the Nigerian 2015 General Election: A Study of â€œPolitics Todayâ€. - Suleiman, Murkthar Muhammad; Ogakason, Rasheed Oshoke; Faruk, Nanoh Bello (NIU Journal of Humanities, 2018)
The mass media, especially the television medium has been found to be a powerful tool in shaping public opinion. The Nigerian political environment is one aspect the media cannot be silent about the study seeks to establish the influence of the television political programme (Politics Today) on the voting opinion of ABU undergraduate students in the 2015 general elections. The objectives of this study were to evaluate the frequency level of ABU undergraduate students viewership of Television political programmes, examine the level of ABU undergraduate students viewership exposure of and â€œPolitics Todayâ€ television political programme during the Nigerian 2015 general elections and determine the influence â€œPolitics Todayâ€ television political programmes on the voting opinion of ABU undergraduate students in the 2015 general election. The survey method was used. Questionnaire was designed and used as the research instrument. A total of 270 copies of questionnaire were distributed to respondents from six selected faculties in the university, out of which 260 copies were returned. Findings of the study show that ABU undergraduate students watch the programme occasionally and the programme influenced the voting opinion of the students in the 2015 general elections. Thus, it was recommended that television stations in Nigeria should produce more political programme to increase political awareness and also broadcast these programme on the internet for wider outreach.